POLA ASUH ORANG TUA DALAM MEMBENTUK KEMANDIRIAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA LEMBURSITU KOTA SUKABUMI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe parenting styles in fostering independence among children aged 4-5 years at TK Negeri Pembina Lembursitu, Sukabumi City. The research employed a qualitative approach with a case study design to obtain an in-depth understanding of parenting practices implemented by parents and their influence on children’s independence development. The research subjects consisted of the school principal, classroom teachers, and parents selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that children’s independence is developed through consistent habituation processes within both family and school environments. Democratic parenting style was found to be more effective in fostering children's independence as it provides opportunities for children to perform activities independently while still receiving guidance from parents. In contrast, authoritarian and permissive parenting styles tend to be less effective in supporting the development of children's independence. Furthermore, collaboration between parents and schools plays a significant role in strengthening the development of independent character in early childhood. This study contributes to a deeper understanding of the importance of appropriate parenting practices as a foundation for developing children's independence in early childhood education.